Pengaruh Word-of-Mouth (WOM) dan Electronic Word-of-Mouth (eWOM) terhadap Keputusan Pembelian pada Salon Alesha Surakarta - Taufig Dwi Farid Taufig; Satria Veriansyah Wiguna (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of Word-of-Mouth (WOM) and Electronic Word-of-Mouth (eWOM) on purchasing decisions at Salon Alesha Surakarta. This research used a quantitative approach with a total of 100 female respondents who had visited the salon from January to May. The measurement instruments consist of Likert-scale questionnaires covering WOM, eWOM, and purchasing decisions. The data were analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression. The results show that: (1) WOM has a significant positive effect on purchasing decisions, (2) eWOM has a significant positive effect on purchasing decisions, and (3) WOM and eWOM simultaneously influence consumer purchasing decisions. The findings emphasize the importance of managing consumer recommendations and online reviews to strengthen purchasing decisions and customer trust. This research contributes to marketing strategies for micro-scale service businesses, especially beauty salons that depend heavily on interpersonal communication and online reputation.